The Influence of Laboratory Management on the Productivity of Health Laboratory Installations at Bandung Kiwari Hospital - Sumiati, Imas; Martiawan, Rudi; Gustiani, Nenny (PT FORMOSA CENDEKIA GLOBAL, 2024)
A regional general hospital is a health service center owned by a region. There are many types of service issues, one of which is laboratory installation, namely how diseases can be diagnosed early. The infrastructure must be complete because services are not only internal but also external to the MCU (Medical Check Up). Of course, this is something that is very important, both for government institutions as well as other institutions such as educational institutions and others that employ staff, but the service has not been carried out optimally, so internal human resources need to be developed much better regarding effectiveness and efficiency in work which must be optimized. Therefore, this research aims to identify the influence of management on service and provide input regarding MCU marketing. The research method used is a quantitative method with a descriptive approach. The results of this research are that laboratory management influences the productivity of laboratory installations. This can be identified from the correlation between the dimensions of laboratory management and productivity, including the dimensions of planning and quality, the dimensions of efficient management, the dimensions of administration and effectiveness, the dimensions of security and efficiency, the dimensions of maintenance and quality, the dimensions of supervision and effectiveness.